Development of an application to support in‐service training of anesthesiologists on preoperative evaluation in a public hospital in Brazil. Issue 5 (19th March 2019) - Pereira, Ricardo Victor Soares; Kubrusly, Marcos; Nogueira, Ingrid Correia; Gondim, Victor José Timbó; Marçal, Edgar
Abstract: Rationale, aims and objectives: This study investigated the process of construction, use, and field evaluation of a mobile application for teaching in the anesthesiology area. Method: The application was built by using the Co‐Design Methodology, which consists of five phases (scoping, shared understanding, brainstorming, refinement and implementation). A one‐week case study was carried out in a hospital involving 20 participants (medical students and residents). Results: The results of the test indicated that the developed application presented a high level of usability. Conclusions: The students considered it to be a useful tool for training and systematizing the preoperative evaluation.